Efforts to Improve Student's Beginning Writing Ability with the Circ Cooperative Model in Class III SDN 08 Botumoito, Boalemo Regency - Thamrin Kum; Deisky Lapa (Journal of Education Review Provision, 2021)
The formulation of the problem in this research is "How to improve students' basic writ-ing skills with the Cooperative Circ model in class II SDN 08 botumoito, Botumoito Sub district, Boalemo Regency?. The method used is classroom action research with the re-search subject being class II students, totaling 14 students with 11 male students and 3 female students. This research was carried out in the form of cycles and each cycle con-sisted of 4 stages, namely the planning stage, the action implementation stage, the observa-tion stage and the reflection stage. This research showed the students' basic writing ability is still in the low category, this is indicated by the low learning activity of students at the time of initial observation, with a percentage level of 28.57% of 14 students. Therefore, the researchers took action using the Circ Cooperative Model. From the results of research conducted on student learning outcomes in the first cycle, the basic writing ability in-creased compared to the initial observation of 57.14%. While in the second cycle the stu-dents' initial writing ability increased up to 92.85%. Based on research conducted in cycle I and cycle II, it can be concluded that using the Circ Cooperative Model can improve stu-dents' basic writing skills in class II SDN 08 Botumoito, Boalemo Regency, this is seen from the increase in student learning outcomes from 57.14% in the first cycle. to 92.85% in the second cycle.